Group Usability Testing of Virtual Reality-based Learning Environments: A Modified Approach - Chen, Chwen Jen; Lau, Siew Yung; Chuah, Kee-Man; Teh, Chee Siong (Elsevier Ltd., 2013)
Conventional usability testing is usually conducted with several individual participants. In recent years, however, group usability testing is gradually gaining attention. Such approach involves several-to-many participants performing tasks simultaneously, with one to several testers observing and interacting with the participants. This approach is able to generate many useful data within a short period of time. In light with the need to further improve the approach, this paper presents a modified version of a group usability testing and how it can be feasibly used to evaluate the usability of a non-immersive virtual reality-based learning environment. The proposed modified group approach aims to minimize the possibility of data loss during the usability testing process. The effectiveness and efficiency of this modified method was compared to the original approach of group usability testing. The results indicate that the modified group usability testing is more effective and efficient than the original approach as it can collect more critical and significant data with lesser time, cost and effort consumption.